Pola Ketimpangan Pendapatan Antarkabupaten di Aceh: Pendekatan Data SUSENAS - Helmi Noviar; Saiful Badli; Zulbaidi Zulbaidi (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study analyzes the patterns and dynamics of income inequality across districts and municipalities in Aceh Province during the 2022–2024 period using data from the National Socio-Economic Survey (Susenas) published by Statistics Indonesia (BPS). A descriptive-comparative approach was employed with the Gini Ratio as the main indicator to examine spatial variations and inequality trends between urban and rural areas. The results show that Aceh’s Gini Ratio declined from 0.296 in 2022 to 0.294 in 2024, indicating a modest improvement in income distribution. The reduction in inequality mainly occurred in rural areas, while urban regions experienced a slight increase due to the concentration of economic activities among higher-income groups. Banda Aceh and Lhokseumawe recorded the highest inequality levels, whereas Aceh Tengah and Bireuen demonstrated relatively strong income equality. Overall, Aceh remains one of the provinces with low-income inequality in Indonesia but still faces challenges of structural disparities across regions. The findings highlight the need to shift policy orientation from redistributive equality toward productivity-based equality through regional economic integration, empowerment of micro and small enterprises, and the development of inclusive economic sectors to achieve equitable and sustainable growth..